Health profile of paediatric tuberculosis patients on directly observed treatment short course therapy - Bandichhode, Sachin T.; Nandimath, Viresh A. (International Journal of Contemporary Pediatrics, 2016)
Background:Children are especially vulnerable to tuberculosis due to close contact with family members and it is often difficult to diagnose and treat it in young children. The objective of this study was to study clinical profile of paediatric TB patients. To assess outcome of directly observed treatment short course (DOTS) among paediatric TB patients. Methods: A descriptive longitudinal study conducted in all paediatric (1-15 years) patients registered for tuberculosis treatment in city tuberculosis center Solapur during 1st November 2010 to 31st December 2012. A pre-designed, pre-tested structural questionnaire was used for data collection. Physical examination was undertaken after the interview was over. Results:93 paediatric TB patients were registered for DOTS. Male to female patient’s ratio was almost equal. Most of the TB patients (35.56%) were in 01 to 05 years of age group. Most of the patients (91) presented with cough for more than two weeks; with other symptoms like evening rise of fever, dyspnea, loss of appetite, swelling over neck. Out of 93 patients 70 patients had protein energy malnutrition (PEM). 84.95% patients were completed the DOTS treatment, while 3.22% were defaulter and outcome in 1.05% was treatment failure. Conclusions:DOTS completion rate among paediatric TB patients is considerably high, protein energy malnutrition have the association with paediatric tuberculosis.